Phosphorization‐Induced Void‐Containing Fe3O4 Nanoparticles Enabling Low Lithiation/Delithiation Potential for High‐Performance Lithium‐Ion Batteries. Issue 19 (1st October 2019) - Nie, Yan; Zhang, Hang; Zhang, Jinfeng; Wang, Lei; Zhong, Siyu; Wu, Yinglong; Duan, Junfei; Shi, Huimin; Victor, Kipkoech Kirui; Zhang, Guanhua; Duan, Huigao
Abstract: In terms of Fe3 O4 ‐based anodes, enormous academic progress has been achieved over the past two decades; however, even with excellent half‐cell performance, the relatively high lithiation potential and unsatisfactory initial coulombic efficiency (ICE) represent two major barriers to their commercial application, at present. We propose partially phosphorized Fe3 O4 (P−Fe3 O4 ) with interior void spaces induced by phosphorization to enhance the Li + storage property of Fe3 O4 ‐based anodes. P−Fe3 O4 anodes offer a much higher capacity at low potential compared with bare Fe3 O4 electrodes. Additionally, the well‐designed nanostructure with preferable specific surface area prevents the initial irreversible lithium loss, which contributes to a brilliant ICE (80.8 % at 100 mA g −1 ). Moreover, in‐situ X‐ray diﬀraction proves that the formation of the Li x Fe3 O4 phase results from an initial intercalation process. In particular, the output voltage and energy density of P−Fe3 O4 full‐cells are much greater than those of Fe3 O4 full‐cells. In this work, the P−Fe3 O4 full‐cell exhibits a capacity of 680 mAh g −1 at 200 mA g −1 as well as an excellent rate capability of 267 mAh g −1 with a current density up to 1000 mA g −1 . This study presents a new strategy to enhance Li + storage of Fe3 O4 enabling low lithiation/delithiation potential and high ICE, which may oﬀer exciting opportunities toward designing high‐performance full‐cells with commercial cathodes. Abstract : Don′t fill the void : A void‐containing P−Fe3 O4 electrode derived from a phosphorization method exhibits a low lithiation/delithiation potential and high initial coulombic efficiency (80.8 % at 100 mA g −1 ) in the half‐cell. The P−Fe3 O4 //NCM full‐cell delivers a higher capacity (341 mAh g −1 ) than that of the Fe3 O4 //NCM full‐cell (98 mAh g −1 ) in the high voltage range from 4 to 2.6 V as well as a remarkable capacity of 452 mAh g −1 at 200 mA g −1 after 50 cycles.